TINJAUAN HUKUM ISLAM TERHADAP TRANSAKSI PENANGGUHAN BAHAN BANGUNAN DENGAN UANG DI MUKA - Nur Sania Dasopang (Journal Khafi : Journal Of Islamic Studies, 2023)
Building material deferral transactions with advance payment in the context of Islamic law require a careful understanding of sharia principles. This practice, which involves agreeing to postpone payments by providing money in advance, can be carried out in accordance with Islamic teachings if it meets the criteria of fairness, avoids elements of usury, and clearly determines the period of postponement. The principle of prohibition of usury is a crucial point in ensuring the validity of transactions, while the principle of justice and certainty of suspension time is the basis for maintaining balance and fairness between the parties involved. Giving money in advance, as a sign of the seriousness of the transaction, can also be implemented as long as it is in accordance with Islamic ethical principles. In this way, these transactions can be implemented legally, following the values ​​of Islamic law, and providing guidelines for business people to carry out economic activities with integrity and morality.